The Effect of Service Quality and Digital Presence on School Image - alkindi jundi abdurrobinabi; Suwandi Suwandi (UIN Siber Syekh Nurjati Cirebon, 2026)
This research is driven by the phenomenon of intense competition among educational institutions, where schools are required to excel not only in physical services but also in digital existence to maintain a robust image and attract prospective students. The purpose of this study is to identify and analyze the partial and simultaneous influence of Service Quality (X1) and Digital Presence (X2) on School Image (Y) at SMK Negeri Mojoagung. The research method employed is quantitative with a causal associative approach. The population consists of SMKN Mojoagung students, with a sample of 305 respondents selected through Proportionate Stratified Random Sampling. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression supported by SPSS software. The results indicate that: (1) Service Quality has a positive and significant partial effect on School Image (t-statistic = 7.950; Sig. < 0.05); (2) Digital Presence demonstrates a positive and significant partial effect on School Image (t-statistic = 8.250; Sig. < 0.05); and (3) Simultaneously, Service Quality and Digital Presence jointly exert a significant effect on School Image (F-statistic = 155.590; Sig. 0.000). These variables contribute 50.4% (R Square = 0.504) to the establishment of School Image, suggesting that the synergy between excellent service and digital Presence activities is a key strategy in enhancing school reputation.